Prospects of snap beans (Phaseolus vulgaris L.) production and commercialization in Benin - Agoyi, Eric Etchikinto; Ahomondji, Symphorien Essèdjo; Butare, Louis; Nchanji, Eileen Bogweh; Ayi, Sergino; Assogbadjo, Achille; Sinsin, Brice Augustin (Frontiers Media, 2023)
Background Vegetables and fruits are highly recommended in diets because of their nutritional importance. Among those, leguminous vegetables are more important, for low-income countries, because of their protein, mineral contents and potential to increase food security and income. In Benin, snap beans ( Phaseolus vulgaris L. ) are the most consumed leguminous vegetables; however, their production is declining, driving the need to understand the current status of its industry to propose solutions for the revival of the sector. This paper assessed the production system, market value, marketing channels, seed systems, and the constraints associated with Benin’s snap bean production from a gender lens. Methods A semi-structured interview was conducted with 602 bean producers and traders, randomly selected from 12 major vegetable-producing areas across Benin. Results The study found a drastic decline in the production of snap beans, with more than 60% abandonment over the last decade. As a consequence, Benin gets supplied through importations, with the highest importation flow coming from Togo (51%), followed by Burkina Faso (25%), and Ghana (12%). Only 13% of the beans traded are locally produced. The leading causes of the decline were pests and diseases that affected the crops’ yield and quality, causing the local produce to be less valued than the imported ones. Women are heavily involved in marketing but cannot expand their business due to low production and high importation. Discussion The study recommends that integrated pest management (IPM) and new varieties with tolerance to major pests and diseases be developed to address market demand and producers trained in agronomic practices.